Pengaruh Promosi, Perubahan Harga Emas, dan Digitalisasi Terhadap Keputusan Nasabah Menabung Emas di Bank Syariah Indonesia KCP Adam Malik Kota Bengkulu - Aurin Novima Setra; Andang Sunarto; Miko Polindi (Jurnal Masharif Al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to analyze the effects of promotion, gold price fluctuations, and service digitalization on customers’ decisions to invest in gold savings at Bank Syariah Indonesia (BSI) KCP Adam Malik, Bengkulu City. The research employs a quantitative approach using a survey method with 95 respondents selected through purposive sampling. Data were analyzed using multiple linear regression with the assistance of SPSS version 23.The results indicate that promotion, gold price fluctuations, and service digitalization each have a significant effect on customers’ decisions to invest in gold savings, with significance values of 0.000 (< 0.05). Simultaneously, these variables significantly influence customers’ decisions, as evidenced by an F-value of 112.241 and a significance level of 0.000. The coefficient of determination (R²) of 0.787 indicates that 78.7% of the variation in customers’ decisions can be explained by promotion, gold price fluctuations, and service digitalization. These findings confirm that promotion strategies, gold price dynamics, and digital service convenience play an important role in shaping customers’ decisions to invest in gold savings at BSI KCP Adam Malik, Bengkulu City